Uterine Arterivenous Malformation - M.Luthfi Yulson; Mondale Saputra (Universitas Andalas, 2024)
Background : Arteriovenous malformations of the uterus are rare and cause sudden, massive vaginal bleeding. Although rare, arteriovenous malformations can occur after a cesarean section. Patients with uterine arteriovenous malformations commonly manifest vaginal bleeding disorders, ranging from menorrhagia to life-threatening bleeding episodes. Management of AVM is by medication, embolization and surgery depending on the patient's condition. Case : Here we report the case of a 28 year old patient with a diagnosis of Late HPP ec Susp. AVM uteruson P4A0L4 post LSCS + moderate anemia. The patient had a history of caesarean section 2 weeks ago, and the patient was admitted for recurrent bleeding. Discussion : Diagnostic examination found an AVM on surgical scars on the uterus and performed angiography and embolization.The diagnosis of uterine arteriovenous malformation should be considered in patients with secondary postpartum hemorrhage Conclusion : Uterine arteriovenous malformation is a life-threatening disorder because it presents withcomplaints of painless bleeding. This case report reported a patient with uterinearteriovenous malformation which was established through clinical findings and supportingexaminations and ruled out other possible causes of postpartum hemorrhage.